Nutrient and anti-nutrient compositions in different plant fractions of Cajanus cajan forage from Malaysia and Indonesia - Abidinsyah, Dian Agustina; Yaakub, Halimatun; Suyub, Iswan B.; Jusoh, Shokri (Society for Innovative Agriculture, University of Agriculture, 2025)
Cajanus cajan is predominantly farmed as a grain crop, and its seeds are utilized for human food. The foliage can be gathered and fed to livestock, both fresh and preserved. C. cajan fodder is an important forage due to its high output potential and excellent feed quality. Although Malaysia and Indonesia are both in Southeast Asia with tropical temperatures, environmental differences such as soil fertility, humidity, and rainfall can all have an impact on C. cajan plant growth. This study aimed to determine and compare the plant height, yield, and nutritional and anti-nutritional compositions of different plant fractions of C. cajan forage from Malaysia and Indonesia. C. cajan was planted in two distinct locations in Malaysia and Indonesia, with samples taken from randomly selected plants. Harvesting was conducted 12 weeks after planting. An independent t-test was performed on the data for plant height and total dry matter (DM) production. Proximate analyses of the anti-nutritional and Ca and P contents of different parts of C. cajan forage were carried out through ANOVA. Results indicate that plants cultivated in Malaysia are higher (P<0.05), with higher stem and leaf values, resulting in a greater overall yield compared to plants in Indonesia. Additionally, C. cajan grown in Malaysia exhibited higher nutritional contents of neutral detergent fiber, acid detergent fiber, and acid detergent lignin than those grown in Indonesia (P<0.05). The anti-nutritional values of C. cajan grown in Malaysia were higher in phenol, condensed tannin, and flavonoids. In conclusion, the study shows that C. cajan grown in Malaysia has superior growth, yield, and certain nutritional and anti-nutritional contents compared to that grown in Indonesia. These findings suggest the potential for optimizing C. cajan cultivation practices in Malaysia to maximize forage yield and quality.